Three Tales of Gender Equality in a Post-Industrial World - Ariane Aumaitre (Luxembourg Income Study (LIS), 2022)
The last decades have witnessed an unprecedented increase in women's economic independence through higher educational attainment, labor force participation and an increase in the share of female-led households. However, up to date there is a gap in the literature concerning how this increase in independence has translated into women's living standards, measured through disposable income. Using a combination of descriptive analysis, OLS regression and RIF regression based decomposition, this paper has unpacks the relationship between economic independence and living standards, and the driving factors behind it. The analysis unfolds three stories regarding the relationship between increasing economic independence for women across developed economies and women's economic wellbeing. First, a story of emancipation for women at the top of the income distribution, who have seen an increase in their living standards. This is especially the case for highly educated women in dual earner couples. Secondly, a story of compensation and stability of living standards for women at the middle of the income distribution, whose entrance in the labor force manages to balance, at the household level, the decrease in male earnings witnessed during the last decades. And, finally, a story of undelivered promises for women at the bottom of the income distribution, who have experienced a relative loss in their economic wellbeing, especially when belonging to non-traditional family structures such as single mother households. From a welfare state perspective, the analysis suggests that traditional welfare regime classifications cannot fully explain differences in living standards among women.
Keywords: 330; women; inequality; income distribution; welfare states